Prognostic Significance of Preoperative Sarcopenia in Patients With Gastric Cancer Liver Metastases Receiving Hepatectomy - Xiong, Jianping; Wu, Yunzi; Hu, Haitao; Kang, Wenzhe; Li, Yang; Jin, Peng; Shao, Xinxin; Li, Weikun; Tian, Yantao (Frontiers in Nutrition, 2022)
Background: The present work focused on assessing the role of computed tomography (CT) -determined sarcopenia in the prognosis of patients with gastric cancer liver metastases (GCLM) receiving hepatectomy. Methods: We analyzed data collected from GCLM cases who underwent hepatectomy between March 2011 to July 2017. The third lumbar vertebra (L3) level skeletal muscle index (SMI) was analyzed by abdominal CT to determine the sarcopenia before surgery. The thresholds for CT-based sarcopenia of sex-specific L3 SMI were ≤ 34.9 cm2/m2 and ≤ 40.8 cm2/m2 for female and male, separately We determined overall survival (OS) and recurrence-free survival (RFS) by univariate and multivariate analyses. Results: The cohort enrolled altogether 114 patients with GCLM receiving hepatectomy (average age: 62.6 years, male: 79.8%), and 58 (50.8%) patients had sarcopenia. The mean SMI was 34.2 in patients with sarcopenia compared to 42.7 in patients without sarcopenia (P<0.001). The 1-, 3-, and 5-year OS rates in patients with GCLM after hepatectomy were 78.1%, 43.7%, and 34.3%, respectively. The 1-, 3-, and 5-year RFS rates in patients were 49.8%, 33.6%, and 29.3%, respectively. Sarcopenia was related to an advanced age (≥65.0 years) (P= 0.009), reduced BMI (<18.5 kg/m2) (P< 0.001) and number of liver metastases (>1) (P= 0.025). Sarcopenia had a significant associated with the patterns of recurrence (P< 0.001). In addition, patients with sarcopenia had a significant difference in number of liver metastases in comparison with those without sarcopenia (P= 0.025). We discovered from multivariate analysis that sarcopenia independently predicted RFS (hazard ratio [HR]= 1.76; 95% confidence interval [CI]= 1.18-2.35, P= 0.007). Nevertheless, sarcopenia was not the prognostic factors that independently predicted OS (HR = 1.62; 95% CI= 0.57–2.73; P= 0.330). Conclusions: In conclusion, we showed that CT-determined sarcopenia was the facile and effective prognostic factor for RFS in patients with GCLM after hepatectomy. Patients with sarcopenia are associated with an increased tumor recurrence risk, and thereby customized treatment should be applied.